The Impact of Human Resources Management Digital Applications on Enhancing the Institutional Excellence: An applied Study on the Department of Economic Development in Ajman Government - Usrof, Hamed (The Arab Journal of Administration, 2020)
This study aimed to investigate the impact of digital human resource management applications in enhancing institutional excellence by applying to the Department of Economic Development in the Government of Ajman in the United Arab Emirates, A specialized questionnaire was developed for this purpose that was distributed to employees of the Department of Economic Development in Ajman through a random sample that reached (99) employees, the data was analyzed using SPSS program. The study concluded that there is an effect of digital recruitment, digital training, and digital assessment on enhancing institutional excellence, and it was found that digital recruitment has the greatest impact from other variables on enhancing institutional excellence. The study recommended the adoption of digital human resource management applications in institutional work, the employment of digital recruitment applications, digital training, and digital evaluation in human resource management operations because of their role in promoting institutional excellence.